WUWUNGAN SEBAGAI SUMBER IDE PENCIPTAAN LAMPU DUDUK KERAMIK - Yustana, Prima (Acintya, 2023)
Wuwungan which was originally functioned as part of the roof of a building will be transformed into another form, namely a sitting lamp. The transformation of the wuwungan into a sitting lamp raises several problem formulations related to how the process is made, how the technical completion of the innovation of roof decoration products into functional objects in the form of a sitting lamp, and whether the character of the sitting lamp inspired by the shape of the wuwungan can increase the atmosphere of beauty of a room.The purpose of this research itself is to find out how the difficulty level of making a sitting lamp is by taking ideas from wuwungan, knowing the process of creating functional works of art in detail step by step, knowing how to innovate sitting lamp products by deforming the real shape of the wuwungan, and creating works of art that are pleasing to the eye. innovative sourced from the strength of local genius.The expected benefits can be a guide for craftsmen or artists who will make innovative ceramic works, provide development in the form and type of product, in order to stimulate the creativity of artists and craftsmen in responding to traditional culture so that they can become innovative and interesting works. The research method used is the method of creating works of art by SP Gustami, namely three stages and six steps in the creation of craft works including exploration, design and embodiment.  Keywords: Wuwungan, Ceramics, Sitting lamp